2010
DOI: 10.1176/ps.2010.61.6.598
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcomes and Costs at Specialized Centers for the Treatment of PTSD After the War in Former Yugoslavia

Abstract: The recovery rate among patients treated in specialized centers for war-related PTSD several years after the war was poor (14%), and symptom improvements were small. The recovery rate was not linked to service costs. Improving recovery rates might require different treatment methods or different service models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Indeed, in analyses excluding the combat involvement variable, the gender of the individuals became significant (available from authors). In a previous study from the area, age was found to have a positive impact on resource use [23]. Neither war-related traumatic experiences nor mental health status were related to use of healthcare services.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Indeed, in analyses excluding the combat involvement variable, the gender of the individuals became significant (available from authors). In a previous study from the area, age was found to have a positive impact on resource use [23]. Neither war-related traumatic experiences nor mental health status were related to use of healthcare services.…”
Section: Discussionmentioning
confidence: 67%
“…The data presented here, relating to the countries of former-Yugoslavia, on the recent use and costs of healthcare services and the factors that influence them highlight these long-term implications of wars. Based on smaller and more selective samples, we have previously reported the costs of services for those who have not actively sought specialist treatment and those who have been in receipt of such care [23], [24]. This is the largest study we are aware of to assess the healthcare service use and costs for populations affected by war, regardless of whether they actively participated in the war or not and if they stayed in the conflict zone or migrated.…”
Section: Discussionmentioning
confidence: 99%
“…Patients are more satisfied with their mental health than with their financial situation, and the experience of unemployment has a dominating influence on their SQOL and treatment satisfaction. An association between employment and SQOL has been well documented in other studies for patients with schizophrenia, mood disorders and neurotic disorders (Priebe et al 2010b). At the same time patients value the therapeutic relationships with staff in the centres.…”
Section: Patient Reported Outcomesmentioning
confidence: 64%
“…In a study that compared the medical cost of PTSD patients with patients with other depressive or anxiety disorders, PTSD was associated with the greatest cost, which was 60% higher than patients with no psychiatric diagnosis (Marciniak et al, 2005), findings that are supported in an HMO setting (Walker et al, 2003) and in male veterans (Chan, Cheadle, Reiber, Unutzer, & Chaney, 2009). Yet in samples of acute PTSD (O'Donnell, Creamer, Elliott, & Atkin, 2005;Priebe et al, 2010), there is no evidence of increased health care-related costs. Therefore, PTSD is associated with greater medical costs, especially when it is chronic, indicating that there are substantial societal consequences to PTSD.…”
Section: Medical Care Use In and The Cost Associated With Ptsdmentioning
confidence: 99%
“…We also suggest that resilience of psychological and physical health is best attained through integrative interventions that initiate change in multiple factors, resulting in substantial change that promotes health of the individual, as well as the social systems in which they reside, resulting in sustainable changes. Last, we assert that interventions at the physiological and cellular levels that reduce PTSD will also have lasting positive effects on families, communities, and society as a whole, which incurs the associated elevated medical costs (Marciniak et al, 2005;O'Donnell et al, 2005;Priebe et al, 2010;Walker et al, 2003), reduced employment productivity (Kimerling et al, 2009;Nandi et al, 2004), and parental and marital difficulties associated with PTSD (Fontana & Rosenheck, 2010;Gangi, Talamo, & Ferracuti, 2009;Kelley et al, 2010). In this article, we highlight the physiological and cellular factors that contribute to resilience and risk following trauma and describe how regulation of inflammation through these mechanisms results in resilience (see Tables 1 and 2).…”
Section: The Cells To Society Resilience Model To Design Novel Intervmentioning
confidence: 99%